SISTEM PAKAR PEMBAGIAN HAK WARIS BERDASARKAN HUKUM ISLAM BERBASIS ANDROID DENGAN METODE FORWARD CHAINING - Ahmad Fatoni; Muhamamd Zainuddin; Marwan Hakim (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2021)
Indonesia is one of the countries with the largest population in the world. Nearly 85% of Indonesia's population is Muslim. One of the problems faced by the majority of the Indonesian population, especially those who are Muslim, is the problem of the distribution of inheritance rights. Many Muslims no longer use the inheritance distribution system according to Islamic Shari'a due to the lack of heirs and lack of knowledge about the distribution of inheritance rights according to Islam so that inheritance issues are often a trigger for disputes that lead to flattening family relations. On the other hand, currently the technology that is developing rapidly is Android technology. Almost everyone has an Android-based mobile phone. Android itself is an operating system that runs on smartphones and adjusts specifications from low-end to high-end classes. Almost all vendors are currently developing their products with the Android operating system because the demand is increasing sharply. Based on the problems and conditions above, an expert system application for the distribution of inheritance based on Islamic law based on Android was made with the forward chaining method, which can help solve the problems faced by the community above